Розвиток і формування особистості засобами літературного виховання - Приймас, Наталія (Видавництво Львівської політехніки, 2013)
В статье рассматривается художественная литература как искусство слова в контексте проблем воспитания и развития личности. Проанализировано комплекс задач литературного воспитания, в частности пробуждение потребности в эстетическом самообразовании и самовоспитании. Обосновано необходимость изучения личности писателя для воспитания средствами художественного слова. Анализируя влияние художественного произведения на духовный мир личности, доказано, что выбор и усовершенствование методик знакомства с литературой как видом искусства для формирования личности читателя является актуальной проблемой современного учебно-воспитательного процесса. The fiction as an art of word in the context of the problems of bringing up and developing the personality is under consideration in the article. The author analyses complex of tasks of literature upbringing, in particular awakening the need of aesthetic self-education and self-upbringing. The paper substantiates the necessity of studying the writer’s personality for upbringing by means of the art of word. Analyzing the influence of the work of fiction on the personality’s spiritual world, it is proved that the choice and improvement of the methods of getting acquainted with literature as a kind of art for the formation of the reader’s personality is considered to be the current problem of modern education and upbringing process.
Развитие и формирование личности средствами литературного воспитания
Development and formation of a personality by means of the literary education
Keywords: литературное воспитание; художественное слово; читатель; развитие личности; literature upbringing; artistic word; reader; forming the personality